Control interno y gestión administrativa en los organismos no gubernamentales en el departamento de Loreto en el periodo 2024 - Rodriguez Tamani, Ruddy Genith (2025)
This research analyzes the relationship between internal control and administrative management in Non-Governmental Organizations (NGOs) in the Loreto region during the 2024 period. A quantitative, correlational, and non experimental design approach was used, with questionnaires applied to 384 NGO workers in the region. Using Spearman's correlation, the results confirmed a significant positive relationship between internal control and administrative management, with a coefficient of 0.743. Additionally, specific hypotheses were validated, examining the influence of control activities on regulatory compliance, the relationship between internal communication and staff satisfaction, and the impact of risk evaluation on operational efficiency. These findings highlight the importance of integrating internal control systems, promoting effective communication, and proactively managing risks to optimize organizational performance. The research concludes that strengthening these aspects is essential to ensure the sustainability and transparency of NGOs in Loreto, especially in an environment that demands high levels of efficiency and commitment to the community.